Hypothetical model in testing integrated development of preschool children - Bala, Gustav (Array, 2009)
Abstract: This paper provides systematic presentation of the issues related to methodology, and offers some possible solutions for analysis of different aspects of child development, especially preschool age. These issues are related to the definition, acceptance and preparation of the existing theories on development, which include analysis of the whole child’s self, his/her surroundings, and his/her activities. In addition, this analysis also includes some methodological problems related to sexual dimorphism, heritage-bound and surroundings-bound development, definition of the model of constructs affecting the selection of variables for evaluation of integral development, definition of the population and selection of the subject sample, determination of manifest characteristics and abilities, selection or construction of measuring instruments for their evaluation, appropriateness of the model and method of data analysis, as well as the possibility of designing the potential model of integrated development of preschool children